A Novel ZnO-Methylene Blue Nanocomposite Matrix for Biosensing Application - Shibu Saha; S. K. Arya; S. P. Singh; Vinay Gupta (International Journal of Electrochemistry)
A novel hybrid matrix of zinc oxide-methylene blue (ZnO-MB) has been successfully developed for biosensing application. The introduction of methylene blue into the ZnO thin film leads to reduction in the charge transfer resistance and suggests an increase in the electron transfer capacity of the composite. Glucose oxidase (GOx) was chosen as the model enzyme and effectively immobilized on the surface of hybrid ZnO-MB nanocomposite matrix. Electrochemical measurements were employed to study biosensing response of the GOx/ZnO-MB/ITO bioelectrode as a function of glucose concentration. The low oxidation potential (−0.23 V) of the hybrid bioelectrode, in a mediatorless electrolyte, makes it resistant against interference from other bio-molecules. The low value of Michaelis-Menten constant (2.65 mM) indicates that immobilized GOx retains its enzymatic activity significantly on the surface of nanocomposite hybrid matrix that results in an enhanced affinity towards its substrate (glucose). The ZnO-MB nanocomposite hybrid matrix, exhibiting enhanced sensing response (0.2 μAmM−1cm−2) with long shelf-life (>10 weeks), has potential for the realization of an integrated biosensing device.